Reliability of the tuck jump injury risk screening assessment in elite male youth soccer players - Read, P. J.; Oliver, J. L.; de Ste Croix, M. B. A.; Myer, G. D.; Lloyd, R. S. (The Journal of Strength and Conditioning Research, 2016)
Altered neuromuscular control has been suggested as a mechanism for injury in soccer players. Ligamentous injuries most often occur during dynamic movements, such as decelerations from jump-landing maneuvers where high-risk movement patterns are present. The assessment of kinematic variables during jump-landing tasks as part of a preparticipation screen is useful in the identification of injury risk. An example of a field-based screening tool is the repeated tuck jump assessment. The purpose of this study was to analyze the within-subject variation of the tuck jump screening assessment in elite male youth soccer players. Twenty-five pre-peak height velocity (PHV) and 25 post-PHV elite male youth soccer players from the academy of a professional English soccer club completed the assessment. A test-retest design was used to explore the within-subject intersession reliability. Technique was graded retrospectively against the 10-point criteria set out in the screening protocol using two-dimensional video cameras. The typical error range reported for tuck jump total score (0.90-1.01 in pre-PHV and post-PHV players respectively) was considered acceptable. When each criteria was analyzed individually, kappa coefficient determined that knee valgus was the only criterion to reach substantial agreement across the two test sessions for both groups. The results of this study suggest that although tuck jump total score may be reliably assessed in elite male youth soccer players, caution should be applied in solely interpreting the composite score due to the high within-subject variation in a number of the individual criteria. Knee valgus may be reliably used to screen elite youth male soccer players for this plyometric technique error and for test-retest comparison.